2008
DOI: 10.1002/humu.20676
|View full text |Cite
|
Sign up to set email alerts
|

Gaucher disease: mutation and polymorphism spectrum in the glucocerebrosidase gene (GBA)

Abstract: Communicated by William S. SlyGaucher disease (GD) is an autosomal recessive disorder caused by the deficiency of glucocerebrosidase, a lysosomal enzyme that catalyses the hydrolysis of the glycolipid glucocerebroside to ceramide and glucose. Lysosomal storage of the substrate in cells of the reticuloendothelial system leads to multisystemic manifestations, including involvement of the liver, spleen, bone marrow, lungs, and nervous system. Patients with GD have highly variable presentations and symptoms that, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
552
1
14

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 587 publications
(578 citation statements)
references
References 171 publications
(136 reference statements)
11
552
1
14
Order By: Relevance
“…The HRs for global cognitive impairment in mutation carriers versus noncarriers from the Mantel‐Haenszel procedure were examined for each of the seven independent cohorts. Proportional HRs across studies were homogeneous with I2 = 40.5%, p  = 0.21 by Cochran's Q‐test for heterogeneity, suggesting it was not imperative, though permissible, to analyze “studies” as a random term in order to allow a more‐universal inference.…”
Section: Resultsmentioning
confidence: 99%
“…The HRs for global cognitive impairment in mutation carriers versus noncarriers from the Mantel‐Haenszel procedure were examined for each of the seven independent cohorts. Proportional HRs across studies were homogeneous with I2 = 40.5%, p  = 0.21 by Cochran's Q‐test for heterogeneity, suggesting it was not imperative, though permissible, to analyze “studies” as a random term in order to allow a more‐universal inference.…”
Section: Resultsmentioning
confidence: 99%
“…Since many recombinant mutations caused by unequal recombination between functional GBA and pseudo-GBA have been recently found [6,8], it is very likely that the rate of genotyping will be increased by recombinant mutation studies. In this study, we identified 4 recombinant alleles in 4 patients ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Allelic heterogeneity in GD has been well described [7,8]. To date, more than 270 different GBA mutations have been reported in the Human Gene Mutation Database at the Institute of Medical Genetics in Cardiff (www.hgmd.cf.ac.uk).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 To date, several GBA recombinant mutations, including gene conversion alleles and, less frequently, reciprocal crossing over alleles, have been identified and referred to by various aliases. 5 In this study, we report four GBA recombinant mutations including one novel allele identified in Korean GD patients using a long-range PCR approach.…”
Section: Introductionmentioning
confidence: 94%